2014
DOI: 10.1016/j.clae.2014.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Modern scleral contact lenses: A review

Abstract: Scleral contact lenses (ScCL) have gained renewed interest during the last decade. Originally, they were primarily used for severely compromised eyes. Corneal ectasia and exposure conditions were the primary indications. However, the indication range of ScCL in contact lens practices seems to be expanding, and it now increasingly includes less severe and even non-compromised eyes, too. All lenses that partly or entirely rest on the sclera are included under the name ScCL in this paper; although the Scleral Len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
148
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(166 citation statements)
references
References 57 publications
2
148
0
1
Order By: Relevance
“…Miniscleral contact lenses, a sub-group of scleral contact lenses with a total lens diameter between 15 and 18 mm which rest entirely upon the sclera [1], are sealed to the anterior eye with minimal movement upon blinking or ocular versions. They are primarily used for the correction of irregular corneal optics commonly encountered in keratoconus, keratoglobus or following penetrating keratoplasty, as the post-lens tear layer (the fluid reservoir between the posterior lens and anterior cornea) effectively neutralises the majority of corneal astigmatism [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Miniscleral contact lenses, a sub-group of scleral contact lenses with a total lens diameter between 15 and 18 mm which rest entirely upon the sclera [1], are sealed to the anterior eye with minimal movement upon blinking or ocular versions. They are primarily used for the correction of irregular corneal optics commonly encountered in keratoconus, keratoglobus or following penetrating keratoplasty, as the post-lens tear layer (the fluid reservoir between the posterior lens and anterior cornea) effectively neutralises the majority of corneal astigmatism [2].…”
Section: Introductionmentioning
confidence: 99%
“…However, advances in anterior eye imaging with corneal topography and optical coherence tomography have resulted in a more reliable and accurate fitting process and along with improved lens designs this has led to a subsequent increase in scleral contact lens prescribing [1].…”
Section: Introductionmentioning
confidence: 99%
“…10 Other applications for modern scleral lenses include compensation for high refractive errors, astigmatism among others. 7,11 Short-term comfort, a protective role in severe ocular surface disease, and the possibility to fit severely distorted corneas without compromising corneal integrity are among the main benefits of such lenses. 11 Conversely, the thick partially static postlens tear layer creates tear stagnation and the potential hypoxic effects, 12 which can compromise ocular health over the long term.…”
mentioning
confidence: 99%
“…7,11 Short-term comfort, a protective role in severe ocular surface disease, and the possibility to fit severely distorted corneas without compromising corneal integrity are among the main benefits of such lenses. 11 Conversely, the thick partially static postlens tear layer creates tear stagnation and the potential hypoxic effects, 12 which can compromise ocular health over the long term. However, clinical experience and the peer-review literature 12,13 have confirmed that corneal edema with scleral lenses is not uniform among wearers; there might be interindividual differences in the response to hypoxia as previously reported.…”
mentioning
confidence: 99%
“…Slightly smaller or larger changes in additional focal power may also be desirable and in the solutions described in this review, these are possible by either slightly changing the lens design, or by intermediate switching of the liquid crystal contact lens. The device should be <300 µm thick to ensure that it is comfortable for the user to wear [22]. The switching time of a LC layer will scale with the square of its cell gap, so any LC layers must be kept as thin as possible.…”
Section: Requirements For a Lc Contact Lensmentioning
confidence: 99%